Consuming and disputing Aisha song: the quest for pleasure and Islamic romance in contemporary Indonesia - Syamsul Rijal (Indonesian Journal of Islam and Muslim Societies, 2022)
The increasing consumption of Islamic popular culture in Indonesia has marked the deepening Islamisation among the Muslim majority. Some scholars have observed the interplay between Islam and popular culture among Indonesian Muslim youths. However, only a few scholars have studied how a particular religious product has been debated and contested within a Muslim society. This article examines the conflicting responses over an Islamic song that describes romantic expression between the Prophet and His wife, Aisha. It focuses on three groups: popular preachers, progressive writers, and YouTube audience. This study found that while some Muslim preachers and progressive writers have criticized the song’s lyrics, most Muslim audience keep consuming the song and regard it as an ideal model of Islamic romance as expressed by the Prophet and His wife, Aisha. The various responses from the three groups represent the diversity of Indonesian Muslims with regards to Islam and popular culture. It also suggests that the Muslim consumers do not always follow the opinions of popular religious elites. The popularity of the song has resonated with the increasing aspiration among pious young Muslims who seek the basis of Islamic romance through the lives of the Prophet and His wife.